Acute Effect of Post-activation Potentiation on Semi-dynamic Balance in Girl Gymnasts Aged 9–12 - Nazanin Afzali; Mohammadtaghi Amiri-Khorasani; Rohollah Nikoei (Journal of Kerman University of Medical Sciences)
Background: Post-activation potentiation (PAP) is a novel warm-up method shown to improve sports performance. This study aimed to investigate the acute impact of this method on semi-dynamic balance while walking on the balance beam among female gymnasts aged 9–12 in Kerman city.Methods: Twenty healthy gymnasts volunteered to participate (height: 138.1 ± 5.04 cm; mass: 40.7 ± 3.12 kg) and were randomly divided into two equal sub-groups. The two groups attended the laboratory on two separate days, 48 hours apart. On the first day, the first sub-group performed a general warm-up (GWU), while the second sub-group performed a PAP warm-up. On the second day, the first sub-group switched to a PAP warm-up, and the second sub-group switched to a GWU. After the warm-up, the subjects took a two-minute rest, and then they walked on the balance beam while their movements were recorded using six motion analyzer cameras that captured the kinematic data of the shoulder, thigh, knee, and ankle joints. The data were processed using a low-pass Butterworth filter and analyzed using one-way ANOVA and paired t tests.Results: The results showed significant differences in shoulder, hip, knee, and ankle joint positions in proximal-distal movements following GWU and PAP warm-ups (P ≤ 0.001). In addition, PAP caused a significant decrease in shoulder, hip, knee, and ankle joint positions in medial-lateral movements compared to GWU (P ≤ 0.001, P ≤ 0.001, P ≤ 0.038, P ≤ 0.001, respectively).Conclusion: PAP warm-up positively affects semi-dynamic balance factors in gymnasts. Given the importance of balance in gymnastics, PAP warm-up is recommended to improve sports performance.